Intersphincteric completion proctectomy with omentoplasty for chronic presacral sinus after low anterior resection for rectal cancer. (2nd February 2016) - Musters, G. D.; Borstlap, W. A.; Bemelman, W. A.; Buskens, C. J.; Tanis, P. J.
Abstract: Aim: This study aimed to determine the clinical outcome of salvage surgery without restoring continuity for symptomatic chronic presacral sinus after low anterior resection (LAR) for rectal cancer. Method: Out of a prospective cohort of 46 patients with chronic presacral sinus (> 1 year after LAR), 27 underwent completion proctectomy with omentoplasty between January 2005 and July 2014. Results: The initial treatment for rectal cancer included neoadjuvant radiotherapy in 26 (96%) patients. Besides a chronic presacral sinus, a secondary fistula was present in 15 (56%) patients. Definitive salvage surgery was performed after a median of 40 (12–350) months from the primary resection. The median hospital stay after single‐ and multiple‐stage salvage surgery was 11 and 17 days. Postoperative complications occurred in 44% of patients. The re‐intervention rate was 33% with a range of 1–10 interventions per patient. During a median follow‐up of 20 (4–45) months from salvage surgery, healing of the chronic presacral sinus occurred in 78% of patients, with a healing rate after single‐ and multiple‐stage procedures of 88% and 64% respectively ( P  =   0.19). Conclusion: Patients with a symptomatic chronic presacral sinus after LAR for rectal cancer, in whom restoration of continuity is not intended, can be effectively managed by completion proctectomy with complete debridement of the sinus and fistula tracts followed by an omentoplasty to fill the presacral cavity, preferably as a single‐stage procedure.